Teachers as School-Based Mentors for At-Risk Students: A Qualitative Study - Simões, Francisco (2013)
Background: Over the past decade, administrators have implemented school-based mentoring (SBM) programs in schools across several western countries. However, few studies have compared the views of mentors and parents regarding the factors that determine SBM success. Objectives: The purpose of this work is to explore the factors that may facilitate or undermine the completion of SBM goals, according to the perspectives of both mentors and parents. Methods: We conducted a qualitative study using the focus group technique, followed by a content analysis. The study involved 22 mentors and 16 parents. We then classified the emergent themes as either facilitators of or barriers to SBM success. Results and Conclusions: The participants focused on how the relationships of mentors with parents, teachers and, more rarely, with social service officials affected the SBM accomplishments. The participants seldom regarded the characteristics of the mentees as an important influence on mentoring effectiveness. Our findings suggest that mentoring delivered by teachers may help to address some of the practical limitations of SBM programs. However, the overlap of mentoring and teaching roles in SBM may also necessitate additional care regarding the definition of purposeful interactions of the mentors with the other adults who are significant in the lives of the mentees, namely their parents and teachers.